La nuit mamelouke.Contribution à l’histoire du quotidien au Caire et à Damas à la fin du Moyen Âge - Mathieu Eychenne (Revue des Mondes Musulmans et de la Méditerranée)
Historians of medieval Islamic society have not paid the same attention to night activities as a topic for social history, as have specialists of the medieval west. Examining cases and narrative sources in Cairo and Damascus, this paper presents the complex reality of a Mamluk city that cannot be reduced to the dangers felt by its inhabitants at nightfall. A public lighting system and night markets in the Mamluk city facilitated circulation throughout the evening and for a great part of the night. Public spaces were monitored and controlled by authorities and neither Cairo nor Damascus should be seen as enclosed and partitioned spaces. Commercial exchanges, public entertainment and traffic contributed to extend daytime activities beyond nightfall and to cast the urban space as a place of socialization. Besides, Mamluk power and religious authorities also invested the city through celebrations and ceremonies performed by night which often turned into popular festivals and outlets while urban elites considered night-time as an opportunity to perfect their social role in a more intimate way and to provide evidence of their elevated status. This paper describes the broad range of individual and collective night practices and restores these activities to their rightful place in Cairene and Damascene daily life.